WORKSHOP MANAJEMEN PEMBELAJARAN ABAD 21 BAGI GURU SMAN 15 BENGKULU UTARA - Dewi, Citra; Rita Prima Bendriyanti; Dicky Rachmadany; Kiki Handika; Rafli Illahi (JURNAL ABDIMAS SERAWAI, 2024)
21st century learning displays significant differences in the learning system, curriculum, reading materials, mindset and character of students when compared to previous eras. Synonymous with technology, both as a learning medium and for evaluation, the 21st century demands the integration of technology in the learning process. Rapid progress and change create new challenges for learners, requiring rapid adaptation of learning management systems. In this context, teachers must be able to innovate, integrate technology with the curriculum, and motivate students to learn independently, creating a learning environment that is dynamic and responsive to current developments. Therefore, the Dehasen University Bengkulu FKIP Lecturer and Student team held a 21st Century Learning Challenges workshop for teachers at SMAN 15 North Bengkulu. The aim of this activity is to provide new understanding and disseminate information to teachers at SMAN 15 North Bengkulu about 21st century learning methods adapting technology and facilitating collaborative learning. Apart from that, this workshop also discussed that teachers are not only educators and must be able to play a supporting role to develop students' critical and creative skills at SMAN 15 North Bengkulu. Fun education can increase student involvement in learning, develop creativity, and bring positive perceptions to the learning process at school. As a result of this activity, teachers are able to motivate students to be active in studying, creating and enthusiastic about facing the challenges of 21st century learning. Character and mindset can be formed and honed by studying, collaborating and innovating. Keywords: Learning Management, 21st Century